The evolution of educational wage differentials for women and men, from 1996 to 2019 - Jessica Ordemann; Friedhelm Pfeiffer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
This paper studies the evolution of three higher education wage differentials from 1996 to 2019 in Germany, a period when significant changes in the educational composition of the workforce took place. Based on regression analysis and samples of male and female workers from the Socio-Economic Panel Study, the study finds that while all three educational wage differentials increased, workers graduating from universities experienced an inverted u-shape pattern, reaching a plateau between 2011 and 2015. We argue that the decline which began after 2015, and which is detectable as well in the occupational prestige scores, may have resulted from a relative educational upskilling of the workforce as well as changes in the subject-choice composition of graduates. We also document differences between East and West Germany that appear to level off over time. The paper concludes with open questions related to these findings and potential future developments.
Keywords: J31; J16; I23; J62; E24; 330; Educational Wage Differentials; Gender Gaps; Higher Education Expansion; Occupational Prestige; Participation